2016
DOI: 10.1002/mds.26488
|View full text |Cite
|
Sign up to set email alerts
|

Cdk5-Dependent Activation of Neuronal Inflammasomes in Parkinson's Disease

Abstract: Together, our results indicated that Cdk5-dependent activation of neuronal inflammasomes was involved in the progression of PD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 45 publications
4
64
0
Order By: Relevance
“…Our studies have been consistent with these reports [14], however, we also unexpectedly identified NLRP3 expression in a subset of surviving DA neurons in late stage PD patients and neuronal cell models [40]. Others report inflammasome activity in neurons [27, [49][50][51], but to our knowledge no in vivo studies have examined directly the function of NLRP3 in DA neurons in the context of aging. In this study, we generated mice with the potential for DA neuron specific NLRP3 inflammasome hyperactivity and analyzed the animals throughout aging ( others who report suppression of NLRP3 inflammasome-driven inflammation dependent on the DRD1 dopamine receptor in bone marrow derived macrophages [67].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our studies have been consistent with these reports [14], however, we also unexpectedly identified NLRP3 expression in a subset of surviving DA neurons in late stage PD patients and neuronal cell models [40]. Others report inflammasome activity in neurons [27, [49][50][51], but to our knowledge no in vivo studies have examined directly the function of NLRP3 in DA neurons in the context of aging. In this study, we generated mice with the potential for DA neuron specific NLRP3 inflammasome hyperactivity and analyzed the animals throughout aging ( others who report suppression of NLRP3 inflammasome-driven inflammation dependent on the DRD1 dopamine receptor in bone marrow derived macrophages [67].…”
Section: Discussionsupporting
confidence: 92%
“…Evidence of NLRP3 inflammasome protein expression in neurons has been reported by our laboratory and others[27,40,[49][50][51], however the impact of neuronal inflammasome activity in aging animals has not been analyzed directly. Having identified NLRP3 expression in remaining DA neurons from PD patients and in human neuronal cell lines[40], we established a genetically engineered mouse model to characterize longitudinally the effect of enhanced DA neuron-specific NLRP3 inflammasome activity throughout aging.…”
mentioning
confidence: 98%
“…Evidence of NLRP3 inflammasome protein expression in neurons has been reported by our laboratory and others [27,40,[49][50][51], however the impact of neuronal inflammasome activity in aging animals has not been analyzed directly. Having identified NLRP3 expression in remaining DA neurons from PD patients and in human neuronal cell lines [40], we established a genetically engineered mouse model to characterize longitudinally the effect of enhanced DA neuron-specific NLRP3 inflammasome activity throughout aging.…”
Section: Resultsmentioning
confidence: 93%
“…The neurotoxicity induced by α-synuclein is partially through the activation of CDK5, a key kinase of CNS required for regulating cellular events in neuronal diseases [125], which can effectively participate in controlling inflammasome activation and oxidative stress in PD progression as well [17,126]. Notably, the downregulation of miR-124 in SNpc dopamine neurons of a MPTP-intoxicated PD mouse model has been found to modulate the expression of calpain1/CDK5 pathway proteins [127].…”
Section: Mechanisms Of Mir-124 In Parkinson's Diseasementioning
confidence: 99%